Respuesta :
remember
difference of 2 perfect squares
a^2-b^2=(a-b)(a+b)
(x)^2-(7)^2=(x-7)(x+7)
set to zero
x-7=0
x=7
x+7=0
x=-7
x=-7 or 7
difference of 2 perfect squares
a^2-b^2=(a-b)(a+b)
(x)^2-(7)^2=(x-7)(x+7)
set to zero
x-7=0
x=7
x+7=0
x=-7
x=-7 or 7
Answer:
Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0
Step-by-step explanation:
Solve by factoring.
x2 - 49 = 0Solve by factoring.
x2 - 49 = 0